2022
DOI: 10.3350/cmh.2021.0093
|View full text |Cite
|
Sign up to set email alerts
|

Toward a complete cure for chronic hepatitis B: Novel therapeutic targets for hepatitis B virus

Abstract: Main body (including references): 7535 Main body (excluding references): 4040 Number of table and figure 2 tables and 1 figure

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
41
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 104 publications
0
41
0
Order By: Relevance
“…A recent study from Korea demonstrated that ciclopirox, a synthetic antifungal agent, strongly inhibits viral replication by blocking the HBV capsid assembly. When combined with NAs, ciclopirox significantly reduced the serum HBV DNA level and HBsAg titer in in vitro and in vivo studies [ 218 , 219 ]. Preclinical studies for the same are currently underway.…”
Section: New Drugs For a Functional Curementioning
confidence: 99%
See 1 more Smart Citation
“…A recent study from Korea demonstrated that ciclopirox, a synthetic antifungal agent, strongly inhibits viral replication by blocking the HBV capsid assembly. When combined with NAs, ciclopirox significantly reduced the serum HBV DNA level and HBsAg titer in in vitro and in vivo studies [ 218 , 219 ]. Preclinical studies for the same are currently underway.…”
Section: New Drugs For a Functional Curementioning
confidence: 99%
“…The main concerns regarding these agents include the risk of off-target toxicity, the potential toxicity of the delivery vehicle, and the risk of post-treatment reactivation by remaining cccDNA [ 219 ]. In addition, ALT flare should be monitored during the course of the treatment [ 224 ].…”
Section: New Drugs For a Functional Curementioning
confidence: 99%
“…In 2015 the World Health Organization estimated that more than 250 million people around the globe were chronically infected, which consequently resulted in almost 900,000 deaths every year due to HBV-related liver diseases [ 4 ]. Since this is the seventh highest cause of worldwide mortality, reducing HBV infections and improving the patients’ treatment is currently aimed in many countries [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Various vaccines and anti-HBV drugs are available thereby preventing new infections and treating liver diseases in HBV-positive patients, respectively [ 7 , 8 ]. Still, scientific and medical communities have embarked on a concerted journey to identify new antiviral drugs aimed at curing infection [ 5 , 7 ]. Although numerous host-derived proteins have been identified as major contributors to HBV infection thus far, these findings had limited functional outcomes, most likely due to the poorly understood in vivo structure, topology, posttranslational modification, and biomolecule-related interaction of relevant target proteins [ 5 , 9 , 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Patients who are HBsAg, anti-HBs, and anti-HBc negative do not possess immunity needs vaccination. Patients who are only anti-HBs-positive are immune or have undergone vaccination[98][99][100].…”
mentioning
confidence: 99%